Das Körperwachstum bei Blattläusen (Homoptera, Aphididae) als Ausdruck des Nährstoffangebots in der Wirtspflanze. Teil I. Gegenwärtiger Stand, Probleme und Aufgaben. - Scholze, Peter (Contributions to Entomology = Beiträge zur Entomologie, 1992)
In consideration of some important publications a short outline of investigations in the field of physiology of aphid nutrition carried out up to date is given. With that the practical aspect of investigations to the operation mode of antibiosis is in the limelight. With special regard to cereal cultures it is evident, that in spite of intensive scientific works it was not yet possible to make varieties available wich are provided with genetical determined antibiotic resistance against cereal aphids. It is pointed out, that intensive investigations concerning parasite/host-interactions would be necessary also in the future. Possibilities and prerequisites are discussed how the interested layman can take part in experiments about development, fecundity, wing determination and other important outward shapes in the biology of aphids.